Highly efficient dual-plasmon polymer solar cell incorporating Au@SiO2 core–shell nanorods and Ag nanoparticles. Issue 93 (22nd September 2016) - Ling, Peng; Ran, Zhang; Shufen, Chen; Qin, Zhang; Lingling, Deng; Xiaomiao, Feng; Wei, Huang
Abstract : Au NRs with ultrathin SiO2 shells directly spin-coated onto P3HT:PCBM and dual-plasmon. Abstract : Generally, metallic nanoparticles (NPs) are widely employed in polymer solar cells (PSCs) to enhance power conversion efficiency (PCE) via the localized surface plasmon resonance (LSPR) effect. Herein, a significant performance enhancement is demonstrated in inverted PSCs by incorporating two kinds of metallic NPs on the rear side of photoactive layer. The Au nanorods (NRs) capped with ∼2 nm ultrathin SiO2 shells, with plasmonic absorption peaks of 520 nm for the transverse axis and 615 nm for the longitudinal axis (in deionized water), and 1 nm-ultrathin Ag NPs with an absorption peak of 517 nm, are in sequence spin-coated on a photoactive layer and thermally evaporated onto MoO3 . To the best of our knowledge, this is the first time that Au NRs are directly spin-coated on a photoactive layer. The dual-plasmon device exhibits an improved short-circuit current density ( J SC ) of 10.36 mA cm −2 and an increased fill factor (FF) of 0.64, generating a PCE of 4.11% with a ∼30% enhancement factor compared with that of the reference device. The enhancement is attributed to the light absorption improvement in the photoactive layer over a wide wavelength range of 500–650 nm, induced by the LSPR of Au@SiO2 NRs and Ag NPs. In addition to the excitation of the LSPR effect, the incorporation of Ag NPs into MoO3 also contributes to the increase in FF value through enhancing the electric conductivity of MoO3 .